Towards a New Implementation of Bandpass Filters on Basis of Band-Stop Structures on Dielectric WGM Microresonators - О. Г. Григоренко; О. О. Трубін (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2023)
A new method of constructing band-stop filters based on a system of optical microresonators with whispering gallery oscillations of ultra-high Quality factor (Q) is proposed, which are widely used in various integral filters of the optical wavelength range. To reduce the mutual coupling, the system of microresonators is located on different sides of the regular transmission line. With the help of perturbation theory, an electrodynamic model of filters was developed, which describes a complex system of interconnected microresonators with doubly degenerate types of natural oscillations. The obtained general analytical expressions are used to describe the characteristics of the scattering of natural waves of the line on the system of optical microresonators, which form a band-stop filter or an alternative band-pass filter. The frequency dependencies of the filter scattering matrix were calculated and analyzed. On the basis of the built analytical model, and using the periodicity of the microresonators' own oscillations, with a change in the free spectral range (FSR) value, the possibility of constructing a new class of band-pass filters has been proven. The new filters differ from the known ones in that they simultaneously use two types of natural oscillations of adjacent microresonators. Amplitude-frequency characteristics of filters with different sizes of operating frequency bands are calculated. Based on the comparison of the obtained data, a conclusion about the reduced dependence of the losses of the proposed filters on the bandwidth is made. It is noted that the amplitude-frequency characteristics of the new class of filters are close to linear ones. The obtained practical simulation results allow significantly reducing the calculation time and optimizing complex multi-resonator structures for optical communication systems.